THE EVENT HORIZON: AN EMERGENT CULTUROMETRIC CONSTRUCT EXPLAINING THE DIFFERENT ACADEMIC ATTAINMENTS OF DIFFERENT CULTURES WITHIN THE SAME FORMAL EDUCATION SYSTEM - Boufoy-Bastick, Béatrice (Verbum, 2015)
Why do students from different cultural groups who experience the same education system have marked differences in academic achievement? These differences in academic attainments within the same education system between cultural groups has been a perennial problem affronting our guiding assumptions of equity and meritocracy and many failed solutions have been proffered. Are some cultures genetically more intelligent than others? Have some groups got more material advantages enabling them to make better use of the education offered? Is it a self-repeating history of socio-cultural advantage vs. socio-cultural exploitation? This article explores the cultural differences that influence academic attainments using the bi-ethnic educational context of the Fiji islands. It introduces the methodological construct of Event Horizon to shed light and explain the differences in language didactics. Based on the assumption that pedagogical practices are culturally defined, it shows how the interpretation and operationalization of a same English as a second language curriculum prescribed by the Ministry of Education by two culturally different ethnic groups, the native Fijians and the Indo-Fijians, leads to markedly differential attainment outcomes: this gap is explained by their different education expectations associated with their different Event Horizon. Now, the unsolved question remains: how to value the richness of cultural differences, yet close the attainment gaps.